Pemilihan Kegiatan Pemberdayaan Masyarakat Pada Program Corporate Sosial Responsibility - Suratmodjo, Arwan Chrysdeckie; Vanany, Iwan (Jurnal Ilmiah Teknik Industri, 2018)
Community development (Comdev) is companyâs obligation and responsibility to the community. Advancing the community towards an independent one and preserving the environment through CSR also contribute towards building a corporateâs reputation. Proper is an award granted by the Ministry of Environment, while PROPER Emas (Gold Proper) is the highest-rank award with a significant impact on the companyâs reputation. Community development programs are essential in achieving PROPER Emas. This research selects a community development (comdev) program suitable to the criteria in oil distribution company using the AHP Expert Choice method, so that the corporate obtains recommendations and a framework to be used for the comdev program. A superior program is necessity for the PROPER Emas judgement, and this research recommends community development activities to be featured as the superior program. This study concludes that the suggested top program to be carried out by fuel oil distribution companyis the eco-friendly waste bank as a first priority, and the river bank forest program as the second. This research expects to feed into the corporateâs CSR programs towards achieving gold proper.